Una implementación computacional del método VEM mixto para el problema de Brinkman en 2D - Sequeira, Filander A. (2019)
In this paper we describe some specific aspects on the computational implementation of the a mixed virtual element method (mixed-VEM) for the two-dimensional linear Brinkman model with non-homogeneous Dirichlet boundary conditions. The formulation used below was originally proposed and analysed in CÁCERES, E., GATICA, G.N. AND SEQUEIRA, F.A., A mixed virtual element method for the Brinkman problem. Math. Models Methods Appl. Sci. 27 (2017), no. 4, 707–743. The implementation presented here consider any polynomial degree k >= 0 in a natural way by building several local matrices of small size. In addition, an algorithm is proposed for the assembly of the associated global linear system, which guarantees the continuity of the normal component in the discrete solution.